Phenolic Compounds in Food Characterization and Health Benefits - Nardini, Mirella (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Phenolic compounds in food such as fruits, vegetables, wine, spices, and oils have been characterized and their possible effects on human health has been studied in depth. Several technological aspects have also been considered concerning the sustainable extraction of phenolic compounds, the long-term storage effects, and the influence of fermentation and boiling techniques on their properties.